Effect of governance, risk management and compliance on a firm’s value (healthcare industry) - Sula Yosege Sembiring Kembaren; Gunardi Endro; Okder Pendrian (Institute of Computer Science (IOCS), 2022)
A high firm’s value is one of the main goals of investors. Management will seek to optimize all factors that have the potential to increase the firm’s value, including the GRC component. The healthcare sector is one of the industries that has shown good performance in several years, including during the crisis due to the Covid-19 pandemic. This pandemic is considered a catastrophic event. Using the explanatory quantitative method, this research aims to prove the difference in the effect of GRC on firm value through two different conditions, before and after the pandemic. The firm’s value is proxied by Tobin's Q, and GRC is measured based on the Indonesian GRC Award scoring method. Through purposive sampling technique on the population of the healthcare industry, as many as 22 companies listed on the Indonesia Stock Exchange, this research took a sample of 11 companies with data sources from 2018 to 2021. The data was processed using a simple linear regression statistical model. The study results show that GRC positively affects firm value, with an explanatory level of 33.8% in pool data. Based on data segregation, the results show that the explanatory level during the pandemic period is more significant.